Emergency pulpotomy in relieving acute dental pain among Tanzanian patients - Simon Elison NM; Matee Mecky I; Nyerere Joachim W (BMC, 2006)
Abstract Background In Tanzania, oral health services are mostly in the form of dental extractions aimed at alleviating acute dental pain. Conservative methods of alleviating acute dental pain are virtually non-existent. Therefore, it was the aim of this study to determine treatment success of emergency pulpotomy in relieving acute dental pain. Methods Setting: School of Dentistry, Muhimbili National Hospital, Dar es Salaam, Tanzania. Study design: Longitudinal study. Participants: 180 patients who presented with dental pain due to acute irreversible pulpitis during the study period between July and August 2001. Treatment and evaluation: Patients were treated by emergency pulpotomy on permanent posterior teeth and were evaluated for pain after one, three and six week's post-treatment. Pain, if present, was categorised as either mild or acute. Results Of the patients with treated premolars, 25 (13.9%) patients did not experience pain at all while 19 (10.6%) experienced mild pain. None of the patients with treated premolars experienced acute pain. Among 136 patients with treated molars 56 (31%) did not experience any pain, 76 (42.2%) experienced mild pain and the other 4 (2.2%) suffered acute pain. Conclusion The short term treatment success of emergency pulpotomy was high being 100% for premolars and 97.1% for molars, suggesting that it can be recommended as a measure to alleviate acute dental pain while other conservative treatment options are being considered.